المحكمة الجنائية الدولية بين مبدأ السيادة و حماية حقوق الإنسان - عوني, حياة (جامعة الوادي University of Eloued, 2019)
حاول المجتمع الدولي منذ قرن من الزمن وضع نسيج متكامل من المعايير الأخلاقية و القانونية التـي تضمن حماية حقوق الإنسان، و كانت المحكمة الجنائية الدولية، أو ل هيئة دولية دائمة تتمتع بتقديم الأفراد المسؤوليــــن عن أسوأ انـــتهاكات حقـــوق الإنـــسان و القانون الدولي الإنساني إلى العدالة، لكن التخوف ظل ينتاب الكثيـر من الدول نظرا للإشكالات التـي أثارها نظام روما الأساسي مع سيادة الدولة. و يركز هذا الموضوع على تحديد المحاور التـي يتحقق بها التوازن بين مهام المحكمة الأساسية و بين التمسك بقدسية مبدأ السيادة الوطنية. For a century, the international community has tried to develop an integrated system of ethical and legal standards protecting human rights .The International Criminal Court,or a permanent international body has been able to bring to justice those individuals responsible for the worst violations of human rights and international humanitarian law. Many States remained apprehensive because of the problems raised by the Rome Statute with the sovereignty of the State. This topic focuses on identifying the axes in which the basic functions of the Court are balanced, and between the adherence to the sanctity of the principle of national sovereignty.
Keywords: المحكمة الجنائية الدولية؛ مبدأ السيادة؛ حقوق الإنسان